The role of headquarters in managing multiple network interdependencies in the context of international sales activities - Sartorius-Khalapsina, Anastasia (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2024)
Literature on networks often assumes that the role of the corporate HQ is less prominent in multinational enterprises (MNEs). We challenge this logic by examining the role of HQ in the management of multiple network interdependencies. The empirical study presented herein is based on three in-depth case studies of French MNEs in the B2B sector. The findings provide insights into the nature of interdependencies between external customer networks and MNE subunits in the context of international sales activities. They furthermore emphasize the central role of the HQ in coordinating multiple inter-organizational relationships and integrating MNE subunit activities, while arbitrating underlying multilateral collaborative tensions among subsidiaries.